Kejahatan Lintas Negara Perdagangan Orang: Studi Kasus Pekerja Migran Asal Nusa Tenggara Barat - Rustam, Ismah; Sabilla, Kinanti Rizsa; Rizki, Khairur; Estriani, Heavy Nala (Universitas Diponegoro, 2022)
This article examines victims of human trafficking from the province of Nusa Tenggara Barat (NTB). Existing research on human trafficking has been studied in general terms and rarely includes Indonesian migrant workers. In fact, perpetrators of human trafficking targeted migrant workers. This research was conducted using a qualitative descriptive method and literature study which aims to describe human trafficking of migrant workers from NTB. In addition, this study analyzes underlying factors of human trafficking within the circle of migrant worker groups from the province of NTB. This article employs several concepts as analytical tools, such as the concept of human trafficking and transnational organized crime. This articles contributes to provide recommendation for policy makers in regulating Indonesian migrant workers.